2002
DOI: 10.2307/1423436
|View full text |Cite
|
Sign up to set email alerts
|

Transmitting False Memories in Social Groups

Abstract: In 2 experiments, subjects studied word lists drawn from Roediger and McDermott (1995) and then participated in perceived group recall (PGR) tests that were intended to lead each subject to believe that she or he was participating in collaborative recall in a 4-person group. Some of the lists were followed by PGR tests containing the nonpresented critical word, some lists were followed by PGR tests not containing the nonpresented critical word, and some lists were not followed by PGR tests. Subjects then compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 0 publications
1
39
1
2
Order By: Relevance
“…However, groups did not differ significantly from individuals in recall of nonpresented critical words that were highly associated to presented words. Although social contagion paradigms (Basden et al, 2002;Roediger et al, 2001) in which the false recall of others has increased the false recall of individuals have been cited as evidence for increases in false memory by groups (Gallo, 2006), we found that the results from the social contagion paradigm do not generalize to collaborating groups. In addition, our results contrast with previous results with recognition in which collaborating groups reduced false alarm rates, relative to individuals (Clark et al, 2000, with 3-person groups; Rajaram & Pereira-Pasarin, 2007).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…However, groups did not differ significantly from individuals in recall of nonpresented critical words that were highly associated to presented words. Although social contagion paradigms (Basden et al, 2002;Roediger et al, 2001) in which the false recall of others has increased the false recall of individuals have been cited as evidence for increases in false memory by groups (Gallo, 2006), we found that the results from the social contagion paradigm do not generalize to collaborating groups. In addition, our results contrast with previous results with recognition in which collaborating groups reduced false alarm rates, relative to individuals (Clark et al, 2000, with 3-person groups; Rajaram & Pereira-Pasarin, 2007).…”
Section: Discussioncontrasting
confidence: 87%
“…Rajaram and Pereira-Pasarin noted that their materials were not designed to produce false memories, but materials that are so designed (such as the DRM materials) result in an increase in false memory following group collaboration. They cited the group studies that did not involve collaboration (Basden et al, 2002;Roediger et al, 2001) as evidence for an increase in false recall. Similarly, Gallo (2006) cited studies that did not involve group collaboration (Basden et al, 2002;Roediger et al, 2001) as evidence for an increase in nonpresented critical word recall in DRM tasks with group recall.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the recollection of the discussion partner can also influence the participant's memory for the event. Misinformation recalled by the discussion partner is often incorporated into the participant's final individual recall (see, e.g., B. H. Basden, Reysen, & Basden, 2002;French, Garry, & Mori, 2008;Gabbert, Memon, & Wright, 2006;Meade & Roediger, 2002;Roediger, Meade, & Bergman, 2001), especially when the individual feels pressure to conform to the discussion partner's responses (Reysen, 2007). This is true even when the information has been recalled correctly by the participant earlier in the experiment (Gabbert, Memon, Allan, & Wright, 2004).…”
mentioning
confidence: 99%
“…A number of recent articles have examined the impact of working with others on participants' memory performance (see, e.g., Basden, Reysen, & Basden, 2002;Betz, Skowronski, & Ostrom, 1996;Bless, Strack, & Walther, 2001;Gabbert, Memon, & Wright, 2006;Hoffman, Granhag, See, & Loftus, 2001;Meade & Roediger, 2002). Some of these studies have found that adding a social context to more traditional memory paradigms can lead to different results than those obtained using methods in which participants are asked to remember information on their own (e.g., Reysen, 2007).…”
mentioning
confidence: 99%